Deliberation Representation Equity : research approaches, tools and algorithms for participatory processes /: research approaches, tools and algorithms for participatory processes. ([2017]) - Ekenberg, Love; Hansson, Karin, 1967-; (Professor of computer and systems sciences), Danielson, Mats; Cars, Göran
No abstract available